The Concept of Istihsan Abu Hanifah in Indonesian Islamic Family Law (Review of Marriage Registration as an Accumulative Condition) - Moh. Hafid (IHSA Institute, 2022)
Development will never stop. It will always flow along with the continuity of time. Meanwhile, Islam as a religion must also follow developments so that later it is not said to be a dead religion. There are many ways and methods that can be used so that Islam can always be side by side in development. One of them is that the concept of Istihsan popularized by Imam Abu Hanifah is very worthy to be guided in making legal decisions. Marriage registration which was originally not obtained as a condition of marriage, then after developments turned out to be prominent and became a law. It's just that in Indonesia this is only used as an administrative requirement. The effect is also understood to be less important and gives a positive meaning to marriage. So the concept of Istihsan needs to be used as a measure in responding to the requirements in the marriage law in Indonesia. This study uses a literature study that refers to library data. As a result, the Istihsan concept suggests that marriage registration is not only an administrative requirement in a marriage. However, it needs to be added to the standard conditions for the validity of a marriage. This, refers to the benefit and main purpose of a marriage.